2022
DOI: 10.1002/pul2.12173
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status in pulmonary arterial hypertension

Abstract: Nutritional deficiencies have been described in patients with pulmonary arterial hypertension (PAH), such as in iron and vitamin D. However, an extensive description of vitamin and mineral status is lacking and until now there is no data on dietary intake in PAH patients. We analyzed blood samples and determined nutritional intake using a food frequency questionnaire (HELIUS) in a cohort of prevalent PAH patients at a single center in Amsterdam, the Netherlands. Quality of life (QoL) was assessed by the SF-36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…During e‐learning and dietary intervention there was a relation between fluid and sugar intake. This confirms a previously found correlation between these two nutrients in PAH patients 6 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…During e‐learning and dietary intervention there was a relation between fluid and sugar intake. This confirms a previously found correlation between these two nutrients in PAH patients 6 …”
Section: Discussionsupporting
confidence: 92%
“… 25 After the e‐learning and until end of study there was only in 12% of our population deficiencies in vitamin K1 plasma levels, which is remarkable since previous research showed a vitamin K1 deficiency in 60% of the PAH patients. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, nutritional deficiencies, such as those of iron, vitamins D, B12, K1 and selenium [ 181 ], have been found in patients with PAH. The improvement of dietary intake and future research to demonstrate the clinical importance of nutritional interventions are ongoing tasks.…”
Section: Progress In Research and Treatment In Pah With The Potential...mentioning
confidence: 99%
“…Altogether, nutrition and lifestyle interventions may not only improve the quality of life of patients with PAH [ 181 , 182 ], but most likely also prevent development of the disease.…”
Section: Progress In Research and Treatment In Pah With The Potential...mentioning
confidence: 99%